Is ice right? Does cryotherapy improve outcome for acute soft tissue injury? - Collins, N. C. (Emergency Medicine Journal, 2008)
Aims: The use of ice or cryotherapy in the management of acute soft tissue injuries is widely accepted and widely practised. This review was conducted to examine the medical literature to investigate if there is evidence to support an improvement in clinical outcome following the use of ice or cryotherapy.